2021
DOI: 10.1108/ijoem-11-2020-1379
|View full text |Cite
|
Sign up to set email alerts
|

Executive directors' pay-performance link and board diversity: evidence from high free cash flow and low-growth firms

Abstract: PurposeThe purpose of this study is to examine whether board diversity can attenuate weaker executive directors' pay-performance link in high free cash flow and low-growth firms (HFCF_LGRW).Design/methodology/approachThis study employed the Malaysian dataset from 2005 till 2016 and the fixed-effect model to investigate the developed hypotheses. The two-stage least squares method (2SLS) is employed to mitigate endogeneity issues.FindingsThis study finds that a positive association between executive directors' p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
(123 reference statements)
1
3
0
Order By: Relevance
“…However, if companies employ net cash flows for other purposes, for example, investing in property, plant, and equipment, joining other business ventures, paying dividends, they may not have business continuity. This informative value of FCF is in line with previous studies, for instance Sapuan et al (2021), Fu et al (2022, Aburisheh et al (2022), and Tee (2023). The implication of this finding is important.…”
Section: The Informative Value Of Free Cash Flow On Corporate Sustain...supporting
confidence: 91%
See 1 more Smart Citation
“…However, if companies employ net cash flows for other purposes, for example, investing in property, plant, and equipment, joining other business ventures, paying dividends, they may not have business continuity. This informative value of FCF is in line with previous studies, for instance Sapuan et al (2021), Fu et al (2022, Aburisheh et al (2022), and Tee (2023). The implication of this finding is important.…”
Section: The Informative Value Of Free Cash Flow On Corporate Sustain...supporting
confidence: 91%
“…Aburisheh et al (2022) found that FCF, operating cash flow, managerial ownership and financial leverage were related to earnings management. Tee (2023) explored the scenario whether board diversity can reduce weaker executive directors' pay-performance link in high FCF and low-growth firms. The study detected a positive association between executive directors' pay and firm performance with high FCF and low-growth firms.…”
Section: Free Cash Flow Conceptmentioning
confidence: 99%
“…First, following the divorce of managerial responsibility from possession in listed firms, agency theory stresses the importance of executive compensation as an internal corporate governance mechanism that matches shareholders' and professional managers' interests (Chukwuma et al, 2021; Wang et al, 2021; Yang et al, 2020). To prevent exploitation of avalanche of information gap which might be to the disadvantage of dispersed shareholders, the principal‐agent theory posits that executive compensation of professional managers should be tied and benchmarked to observable firm performance of listed firms (Ko et al, 2020; Tee, 2021). This helps to transfer some of the risks to professional managers and instigate them to pursue shareholders' interests.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gender diversity in the workplace and mainly in the boardrooms becoming more attentive area around the globe where the women representation in the boardrooms have been made compulsory in many countries for the reflection of diverse decisions on the market situations for the strategic and financial decisions of the firm (Ajaz et al., 2020; Tee, 2021). The decisions regarding the diversity in board under the moral ground cannot be imposed but these decisions are made on the basis of the concerns of cost benefit analysis for a firm (Sarhan et al., 2019).…”
Section: Introductionmentioning
confidence: 99%